2012
DOI: 10.1038/leu.2012.86
|View full text |Cite
|
Sign up to set email alerts
|

Spliceosome and other novel mutations in chronic lymphocytic leukemia and myeloid malignancies

Abstract: Spliceosome mutations represent a new generation of acquired genetic alterations that affect both myeloid and lymphoid malignancies. A substantial proportion of patients with myelodysplastic syndromes (MDSs) or chronic lymphocytic leukemia (CLL) harbor such mutations, which are often missense in type. Genotype-phenotype associations have been demonstrated for one of these mutations, SF3B1, with ring sideroblasts in MDS and 11q22 deletions in CLL. Spliceosome mutations might result in defective spliceosome asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 72 publications
0
12
0
Order By: Relevance
“…4, 5 Recent groundbreaking discoveries have identified recurrent mutations in SF3B1 (and/or other splicing factors) in multiple forms of cancer including: myelodysplastic syndromes (MDS), 14,28 chronic lymphocytic leukemia (CLL), 29 acute myeloid leukemia (AML), 30,31 breast cancer, 32, 33 lung adenosarcoma, 34 and uveal melanoma. 35 These genetic studies have also fueled complementary research in the therapeutic significance of spliceosome recurrent mutations.…”
Section: Introductionmentioning
confidence: 99%
“…4, 5 Recent groundbreaking discoveries have identified recurrent mutations in SF3B1 (and/or other splicing factors) in multiple forms of cancer including: myelodysplastic syndromes (MDS), 14,28 chronic lymphocytic leukemia (CLL), 29 acute myeloid leukemia (AML), 30,31 breast cancer, 32, 33 lung adenosarcoma, 34 and uveal melanoma. 35 These genetic studies have also fueled complementary research in the therapeutic significance of spliceosome recurrent mutations.…”
Section: Introductionmentioning
confidence: 99%
“…Although treatment has undergone profound improvements in recent years [4][5][6] , CLL shows a remarkable clinical variability which is likely to be reflective of a large biological heterogeneity 7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, recent genomewide sequencing studies revealed that mutations in genes encoding splicing factors are commonly associated with MDS and other hematological malignancies (6)(7)(8)(9)(10)(11)(12)(13)(14)(15). One of these newly identified genes codes for the SRSF2 splicing factor (also known as SC35), and its mutations have been linked to poor survival among MDS patients (16,17).…”
mentioning
confidence: 99%